Effect Of Portable Vacuum Clamping On Acrylic Pocket Machining Performance - Ab Wahab, Norfariza; Samsul Mafrizal, Mohamad Nor Iqbal; Ruslan, Eliyana; Mustafa, Nuzaimah; Abdul Hadi, Dayanasari; Zahari, Madiha; Abd. Mutalib, Nurliyana (Asian Research Publishing Network, 2020)
This project provides a mechanical clamp limitation solution that should not leave marks on the clamped surface and is unable to handle small thickness of workpiece. Using a new method involving a new component that develops dual vacuum clamper to attach and detach the workpiece to the flat surface and is capable of clamping small and thin workpieces. In this project, which is reservoir will help it ability of pocket machining performance with two condition. The two conditions are air pressure from compressor through to vacuum system and one more is no air pressure from compressor. Experiments have been conducted using diameter 2mm HSS end mill and acrylic workpiece on pocket machining. The time required to run the experiment is about 30 minutes. So, the result of experiment had been taken for every 5 minutes. After the experiment, evaluation of thrust force and dimension accuracy also had been conducted. Dynamometer type 9257BAis used to evaluate the thrust force and Horizontal Optic Comparator and Coordinate Measurement Machine for analyze the diameter accuracy. As a result for thrust force, for Fx and Fy axis for both condition was stable however for Fz for both condition produced decline result as time increased. On the other hand, the result also showed that vacuum clamping contributed in better dimension accuracy with average value of 14μm for continuously pressure method and 8μm for maintain pressure method. The average dimension accuracy was produced by taken 13 points selected area on workpiece. For air pressure from compressor through to vacuum system condition, the vacuum capable of clamping the workpiece during the pocketing process which only dropped 1.7kPa from 70.3 kPa. As conclusion, this project had showed that the effectives in clamp during pocket machining using vacuum clamping method.